2019
DOI: 10.1080/16078454.2019.1598679
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygous mutations Glu502Lys and Met527Thr of the FXII gene in a patient with factor XII deficiency

Abstract: Objective: To study the gene mutation of human coagulation factor XII (FXII) in a Chinese family with FXII deficiency and it will help us to understand the pathogenesis of this type of disease. Clinical presentation: The proband was a 50-year-old male who had a fracture of the right humerus. The routine presurgical coagulation test showed a significant prolonged activated partial thromboplastin time (APTT) at 59.1s (reference range, 29.0-43.0s). Techniques: FXII activity (FXII:C) and FXII antigen (FXII:Ag) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The substitution may impair intracellular protein processing and eventually lead to a CRM-negative FXII deficiency. Zhang et al had previously shown Met527Thr mutation to be the cause of FXII deficiency in a family, which is the same site but different mutant amino acid from our study [21].…”
Section: Discussionsupporting
confidence: 44%
“…The substitution may impair intracellular protein processing and eventually lead to a CRM-negative FXII deficiency. Zhang et al had previously shown Met527Thr mutation to be the cause of FXII deficiency in a family, which is the same site but different mutant amino acid from our study [21].…”
Section: Discussionsupporting
confidence: 44%
“…Since its discovery, it has become clear that the contact system is a driving force behind thrombosis and hemoincompatibility (4). Remarkably, deficiency in contact factors does not translate into bleeding disorders (57), suggesting that a function beyond hemostasis justifies the existence of this enzyme system.…”
Section: Introductionmentioning
confidence: 99%
“…Different range genetic testing was performed to test genetic variations of SERPING1. Firstly, Sanger sequencing of the gene coding part (using primers from published manuscript with Big Dye Terminator kit 3.0 following manufacturer protocol) was conducted [17][18][19]. For two cases, exome sequencing (performed using Twist Bioscience reagents at CeGaT medical laboratory) analysis of the single nucleotide variation and copy number variation (CNV) in SERPING1 were done.…”
Section: Genetic Testingmentioning
confidence: 99%